Esoteric Theravada: the story of the forgotten meditation tradition of Southeast Asia - Crosby, Kate 19XX- (Shambhala Publications, Inc, 2020)
The colonial gaze : the invisibility of premodern Theravada meditation -- Abhidhamma and practice : the path in Theravada meditation systems -- Documenting the esoteric : the production and survival of evidence for premodern Theravada meditation -- Technologies of transformation : grammar, mathematics and the significance of substitution -- Transformation of the body : meditation, medicine and chemistry -- From centre to periphery : the changing place of borān kammaṭṭhāna under Thai influence -- Meditation in modern revivals.